Revisiting the Productivity-Hours Puzzle in the RBC Paradigm: The Role of Investment Adjustment Costs - Alice Albonico; Sarantis Kalyvitis; Evi Pappa (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
Conventional RBC models have been heavily criticized for their inability to generate the estimated negative correlations of hours and productivity in response to technology shocks ('productivity-hours puzzle'). In this paper we show that by just enhancing the standard frame- work with investment adjustment costs can resolve the 'productivity-hours puzzle'.
Keywords: E22; E32; 330; technology shocks; productivity-hours puzzle; investment adjustment costs; wealth effect